Intranodal mapping using carbon dye results in more accurate lymph node staging in colon cancer patients - Weixler, Benjamin; Warschkow, René; Zettl, Andreas; Riehle, Hans-Martin; Guller, Ulrich; Viehl, Carsten T.; Zuber, Markus (World journal of surgery, 2015)
Small nodal tumor infiltrates (SNTI)—defined as isolated tumor cells and micrometastases—are associated with worse disease-free and overall survival in stage I and II colon cancer patients. Their detection, however, remains challenging. The objective of the present study was to evaluate whether there is a correlation between the location of SNTI and phagocytosed carbon dye particles in sentinel lymph nodes (SLN) of colon cancer patients.